STRATEGI KAMPANYE POLITIK TIM SUKSES H. Agus Sopyan DALAM PEMENANGAN KEPALA DESA SEGARA MAKMUR TAHUN 2020 DI ERA PANDEMI COVID-19 - Devi Mustafa Putri, (2022)
This study aims to discuss the political campaigns carried out by the H. Agus Sopyan Campaign team in the era of the covid-19 pandemic by using political communication theory, the concept of political campaigns and using 7 indicators as campaign steps according to Cangara, namely, 1. Discovery and determination, 2. Determine the objectives to be achieved, 3. Determining the strategy (a. Determining campaigners, b. Setting targets, c. Composing campaign messages, d. Selection of media) 4. Dissemination of messages through the media, 5. Effect of campaigns, 6. Mobilization influential groups, 7. Scheduling of campaign activities. The method used is qualitative by using primary data sources and secondary data. Data collection techniques used in-depth interviews, observation, and documentation. Data analysis techniques according to Miles and Huberman are data collection, data reduction, data presentation, and drawing conclusions. The final result of this study shows that H. Agus Sopyan's political campaign based on the 7 steps above as a research analysis tool can be concluded that by dividing the team into 3 parts to have a part to bind supporters at the family level this is able to maintain public support for the candidate, and through The preparation of messages with one-side issues in order to convey messages as political communication carried out by the H. Agus Sopyan campaign team proved to be able to maintain public sympathy for the candidates. The campaign aims to convince as many voters as possible with crowd restrictions in the campaign being an obstacle for the campaign team, but in H. Agus Sopyan's political campaign in the 2020 Pilkades in the covid-19 pandemic era the campaign was carried out with crowd restrictions packed with activities favored by the target voters so that they could get to win. Keywords: Political Campaign, Political Campaign Team, Pilkades, Covid-19